Keanekaragaman Jenis Ekhinodermata Di Perairan Minahasa Utara, Sulawesi Utara - Eddy Yusron; Susetiono Susetiono (Universitas Atma Jaya Yogyakarta, 2010)
Observation on echinoderms diversity was carried out at coastal waters of North Minahasa bay, North Sulawesi, from June to August 2008. Sampling was done by using a transect quadrant of 1 m x 1 m. The results showed that in both locations, 28 species of echinoderms represented 7 species of Holothuroidea, 9 species of Echinoidea, 6 species of Asteroidea and 6 species of Ophiuroidea had been found in the North Minahasa Bay, North Sulawesi. The Echinoidea were relatively common in the sea grass zone. On the basis of population density, Echinoidea was the dominant group and had the highest density. This research was aimed to find out the species composition, community structure, zonation, and spatial distribution of echinoderm fauna.